“This Forest Is Our Supermarket” Communicating Sustainability Through The Lens Of Batek Negrito Of Kuala Tahan - Teh, Kate Yng; Hasan, Nik Norma Nik (2015)
The Batek Negrito is one of the Orang Asli groups who primarily inhabit the rainforest in Peninsular Malaysia. This paper attempts to discuss the unique relationship of the Batek with the forest, their daily sustainability practices and their perceptions of development. Arguing that the forest is their native lands, this study also focuses on the impacts of the national park on livelihoods of the aborigines. The data were collected from in-depth interviews with Batek respondents and participant observations at one of the Orang Asli settlements, Kampung Dedari. The findings reveal that the livings of the Batek people were highly inseparably linked to the forest; the forest is their true home with great dependence on the forest resources which they also claimed as their ‘supermarket’. Not just important for food subsistence, it has been found that the forest also shapes their customs, traditions, and beliefs about the spirits of the nature. They also regard themselves as the ‘wildlife’ of the jungle whose protect the natural resources in their care. Although the ecotourism development surrounding Kampung Dedari has been benefiting the Batek in term of economic returns, at the same time it has also put pressure on their natural living environment. Hence, understanding how they communicating their sustainability practices can contribute to even greater understanding of local sustainability discourse which could help preserves the cultural rights of the aborigines, their ‘supermarket’ and the national park, at the same time.